Basil essential oil as an alternative to commercial biocides against fungi associated with black stains in mural painting. (January 2020) - Marco, Alexandra; Santos, Sandra; Caetano, Joaquim; Pintado, Manuela; Vieira, Eduarda; Moreira, Patrícia R.
Abstract: In northern Portugal it was identified that some mural paintings from the 15th and 16th centuries disclose a chromatic alteration in the form of black stains possibly of microbiological origin. In the search for its cause, samples were collected and microorganisms were isolated from selected areas of the pictorial sets of three case studies that displayed dark pigmentation. Four representative fungal isolates were selected due to their pigmentation and growth characteristics – Alternaria alternata, Alternaria tenuissima, TZ10.2.2 (possibly Pestaloptia sp.) and TZ8.2.2 (possibly Penicillium sp.). An attempt was made to encounter an innovative environmentally innocuous and green safe alternative biocide to replace the chemical-based toxic compounds currently in use. Essential oils with confirmed antifungal potential and seldom employed in the conservation of cultural heritage and even less in mural painting ( Rosmarinus officinalis, Foeniculum vulgare, Citrus lemmon, Ocimum basilicum and Salvia officinalis ), were tested against commercial biocides (Benzalkonium chloride, Preventol R80, CaSoPaL® and Durolith®), to evaluate their in vitro efficacy and the determination of the minimum inhibitory concentration. Basil was able to inhibit growth on all tested strains at 1.25 μl ml −1 . From the commercial biocides, Benzalkonium chloride and Preventol R80 were the ones with the best performance but needed higher concentrations than basil to achieve the same result enabling this essential oil a useful alternative to commercial biocides. The literature regarding the use of essential oils in mural paintings is, apart from two known authors, practically non-existent making it a novel approach. Graphical abstract: Image 1 Highlights: 15th-16th century fresco wall paintings are located in N. Portugal granite churches. Black stains chromatic alterations possibly originated by microorganisms. Four fungal isolates selected for in vitro assays with essential oils and biocides. Basil was the only essential oil able to inhibit growth of all fungal isolates. BC and Preventol R80 inhibit growth of all fungi at higher concentrations than basil.